2003
DOI: 10.1093/jnen/62.11.1178
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Brainstem Abnormalities in Northern Plains Indians with the Sudden Infant Death Syndrome

Abstract: The rate of the sudden infant death syndrome (SIDS) among American Indian infants in the Northern Plains is almost 6 times higher than in U.S. white infants. In a study of infant mortality among Northern Plains Indians, we tested the hypothesis that receptor binding abnormalities to the neurotransmitter serotonin (5-HT) in SIDS cases, compared with autopsied controls, occur in regions of the medulla oblongata that contain 5-HT neurons and that are critical for the regulation of cardiorespiration and central ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(157 citation statements)
references
References 25 publications
8
148
0
Order By: Relevance
“…Increased polymorphism frequencies have been identified in 25 genes in SIDS infants compared to controls, 3 of which are serotonin genes (31). Tissue receptor autoradiographic studies of brainstem tissue in SIDS patients have shown arcuate nucleus (30,32) and more widespread brainstem reduction in 5HT 1A binding, increased 5HT cells and reduction in 5HT transporter binding (32,33), suggesting abnormalities in a system prominently Additional information on the serotonin theme comes from animal studies: mice with an audiogenic seizure disorder due to a genetic deletion of the 5HT 2c receptor die in the postictal period if unresuscitated (34). DBA/2 strain mice, which suffer audiogenic seizures, have marked susceptibility to postictal respiratory arrest, which can be reduced when pretreated with selective serotonin reuptake inhibitors (SSRIs) (35).…”
Section: Sleep Arousal and Serotoninmentioning
confidence: 99%
“…Increased polymorphism frequencies have been identified in 25 genes in SIDS infants compared to controls, 3 of which are serotonin genes (31). Tissue receptor autoradiographic studies of brainstem tissue in SIDS patients have shown arcuate nucleus (30,32) and more widespread brainstem reduction in 5HT 1A binding, increased 5HT cells and reduction in 5HT transporter binding (32,33), suggesting abnormalities in a system prominently Additional information on the serotonin theme comes from animal studies: mice with an audiogenic seizure disorder due to a genetic deletion of the 5HT 2c receptor die in the postictal period if unresuscitated (34). DBA/2 strain mice, which suffer audiogenic seizures, have marked susceptibility to postictal respiratory arrest, which can be reduced when pretreated with selective serotonin reuptake inhibitors (SSRIs) (35).…”
Section: Sleep Arousal and Serotoninmentioning
confidence: 99%
“…A major advance in our understanding of the etiology of SIDS has been the finding that many SIDS infants have decreased binding of muscarinic and kainate receptors in the arcuate nucleus at the ventral surface of the medulla (Kinney et al, 1995;Panigrahy et al, 1997) and abnormal binding to serotonergic (5-HT) receptors in the medullary serotonergic nuclei, including the paragigantocellularis lateralis (PGCL) (Panigrahy et al, 2000;Kinney et al, 2003). Dysfunction in these regions may increase the risk for SIDS by altering protective reflexes to stressors encountered during sleep such as hypercapnia, hypoxia, and laryngeal stimulation (Filiano and Kinney, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…5,29 We hypothesize that at least a subset of SIDS is caused by an underlying brainstem abnormality in neural networks that mediate protective responses to asphyxia, resulting in sleep-related sudden death. [30][31][32][33][34][35] In support of this hypothesis, we have reported deficiencies in infants who died of SIDS in interrelated neurochemical parameters in the medullary serotonergic network that plays a key role in protective respiratory or autonomic responses to homeostatic stressors. [30][31][32][33][34][35] The parameters are related mainly to the neurotransmitters serotonin and g-aminobutyric acid (GABA) and the signal transduction family 14-3-3, involved in serotonin regulation.…”
Section: Discussionmentioning
confidence: 60%
“…[30][31][32][33][34][35] In support of this hypothesis, we have reported deficiencies in infants who died of SIDS in interrelated neurochemical parameters in the medullary serotonergic network that plays a key role in protective respiratory or autonomic responses to homeostatic stressors. [30][31][32][33][34][35] The parameters are related mainly to the neurotransmitters serotonin and g-aminobutyric acid (GABA) and the signal transduction family 14-3-3, involved in serotonin regulation. [30][31][32][33][34][35] Given a reduction in the overall SIDS rate associated with an increased rate of supine sleep, 5,[8][9][10] it is highly likely that prone sleep position plays a direct role in the chain of events leading to sudden death in some infants.…”
Section: Discussionmentioning
confidence: 60%